ABOUT INCLUSIVE EDUCATION - Nabiev , Tukhtamurod Sakhobovich (GOLDEN BRAIN, 2024)
ensuring equal access to education for all students, taking into account the diversity of special educational needs and individual capabilities, in particular for people with disabilities, limited ability to live, students with disabilities.